Evaluacion de la poda severa de recepa en cafe robusta ( Coffe canephora Pierre) para mejorar la renovacion de tejido vegetal en la zona de Ventanas,provincia de los Rios. - Muñoz Gavilanez, Diana Katherine (2018)
VIII. SUMMARY The experiment was conducted on the farm of Mr. Mariano Cabrera, located in Los Angeles, canton Ventanas, Los Ríos province. The locality study has the following characteristics: the same ones that were taken with the use of a GPS: an altitude of 117 meters above sea level, at the coordinates Latitude 277438.3 East and Longitude -110598 North, with an average annual temperature of 24ºC / light per year and an average humidity of 80%. The objectives of the study were: to determine the efficacy of recepa at coffee strong pruning and determine the optimal number of bud in plants of robusta coffee in Ventanas. The essay was based on a design of complete randomized blocks, which corresponds to an experiment of five treatments and four replications and the Tukey test was used to test averages. Results mentioned that the pruning of rehabilitation, is a practice that helps the rejuvenation of little productive and aged coffee, also indicated that this pruning sets coffee trees management and planning of reforestation in the area coffee farm. As for agronomic variables, mentioned that major differences in treatments not recorded in the first year of evaluation of coffee after the recepa. Key words: coffee, prune, pruning, sprout, diameter.